Planning, Preparedness and Challenges During COVID-19 Pandemic: Experiences from Emergency Department - Rabin Bom (Journal of Lumbini Medical College, 2020)
Two months have already passed since the declaration of countrywide lockdown on last week of March 2020. The number of corona virus disease (COVID-19) infected cases are gradually increasing in Nepal till date. With a steady increase of COVID-19 cases the burden of planning and preparedness is also getting bigger. Outpatient departments (OPDs) were closed for the first few weeks and all patients visiting the hospital were screened at fever clinic established at the hospital entry point. Suspected COVID-19 cases were then quarantined at special COVID-19 isolation ward using a different route. Those patients whose history excluded the suspicion of COVID-19 were then allowed to proceed to Emergency Department (ED).